Facility standards and the quality of public sector primary care: Evidence from South Africa's "Ideal Clinics" program. (17th March 2021) - Stacey, Nicholas; Mirelman, Andrew; Kreif, Noemi; Suhrcke, Marc; Hofman, Karen; Edoka, Ijeoma
Abstract: Primary healthcare systems are central to achieving universal healthcare coverage. However, in many low‐ and middle‐income country settings, primary care quality is challenged by inadequate facility infrastructure and equipment, limited human resources, and poor provider process. We study the effects of a recent large‐scale quality improvement policy in South Africa, the Ideal Clinics Realization and Maintenance Program (ICRMP). The ICRMP introduced a set of standards for facilities and a quality improvement process involving manuals, district‐based support, and external assessment. Exploiting differential prioritization of facilities for the ICRMP's quality improvement process, we apply differences‐in‐differences methods to identify the effects of the program's efforts on standards scores and primary care quality indicators over the first 12 months of implementation. We find large and statistically significant increases in standards scores, but mixed effects on care outcomes—a small magnitude improvement in early antenatal care usage, null effects on childhood immunization and cervical cancer screening, and small negative effect of human immunodeficiency virus (HIV) care. While the ICRMP process has led to significant improvements in facilities' satisfaction of the program's standards, we were unable to detect meaningful change in care quality indicators.